Beyond Pedagogy: Halaqah and Socio-Epistemic Reproduction of Religious Moderation in West Sumatra, Indonesia - Zainal Asril; Syahril; Duski Samad; Fatmi Fauzani Duski; Taufiq Hidayat (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
While religious moderation is frequently analyzed as a normative state policy or curricular content, less attention is given to the socio-epistemic mechanisms through which moderate dispositions are historically produced and embodied. This study examines the construction and reproduction of religious moderation within the Minangkabau surau–halaqah–pesantren tradition by conceptualizing halaqah as an indigenous epistemic system rather than merely a pedagogical method. Utilizing a qualitative approach framed by Interpretative Phenomenological Analysis (IPA), data were gathered through in-depth interviews, participant observation, and documentary analysis involving tuanku, ustaz, santri, and administrators across five distinct educational sites. Grounded in Berger and Luckmann’s social construction theory and Bourdieu’s concept of habitus, the findings reveal that halaqah operates as a socio-epistemic mechanism integrating ta‘līm (knowledge transmission), tarbiyah (character formation), and tazkiyah (spiritual cultivation) through talaqqī, kitab kuning study, sanad continuity, and adab-based interaction. Within the Minangkabau cultural philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS–SBK), religious moderation is reproduced not as an externally imposed doctrine, but as an embodied disposition mediated by local cultural rationality and transregional Islamic intellectual networks. This study advances Islamic education and sociology of religion scholarship by demonstrating that sustainable religious moderation relies on historically rooted, institutionally embedded systems of knowledge reproduction and ethical habituation.